Taman Baca Tanah Ombak Dalam Meningkatkan Literasi Baca Anak Di Pantai Purus - Aulia Fadila (Fakultas Ilmu Komunikasi Universitas Islam Nusantara, 2020)
This research was conducted in Tanah Ombak Reading Park, Purus III Village, Padang City, West Sumatra. This study aims to illustrate that Tanah Ombak reading park has a considerable influence in changing the stigma and views of the community around Purus Beach which is very far from the reading material and has bad behavior. This is where the role played by the Tanah Ombak Reading Park to make the children of the Purus Beach community have good character and good literacy too. This research uses descriptive research method using a qualitative approach. The purpose of descriptive research is to provide a description based on accurate facts obtained in the field. The subjects in this study were children who lived around Tanah Ombak Reading Park, while the object of the study was Tanah Ombak Reading Park, Padang, West Sumatra. Data collection techniques carried out by observation, interviews and literature. The informants in this study amounted to one person, Mr. Yusrizal. The results of this study are (1) children's reading literacy and society will develop well if the elements that play a role in the scope understand their respective roles (2) many activities held by Tanah Ombak Reading Park to improve reading literacy(3) Tanah Ombak Reading Park has various awards from other renowned institutions and artists. (4) the obstacle felt by Tanah Ombak Reading Park is the lack volunteers so the activities are not well structured. So it can be concluded that Tanah Ombak reading Park has a positive impact in providing education and teaching to children such as learning to count, draw, tell stories, play, and most importantly teach norms in society. However, all activities are constrained due to the limited volunteers so that the activities are only carried out by children independently, such as reading books by themselves without being accompanied by volunteers. Suggestion for the future that Tanah Ombak Reading Park informs the public about the needs of volunteers so that the activities in Tanah Ombak Reading Park can take place in a structured manner.